Bromelain and Nisin: The Natural Antimicrobials with High Potential in Biomedicine - Urška Jančič; Selestina Gorgieva (MDPI AG, 2021)
Infectious diseases along with various cancer types are among the most significant public health problems and the leading cause of death worldwide. The situation has become even more complex with the rapid development of multidrug-resistant microorganisms. New drugs are urgently needed to curb the increasing spread of diseases in humans and livestock. Promising candidates are natural antimicrobial peptides produced by bacteria, and therapeutic enzymes, extracted from medicinal plants. This review highlights the structure and properties of plant origin bromelain and antimicrobial peptide nisin, along with their mechanism of action, the immobilization strategies, and recent applications in the field of biomedicine. Future perspectives towards the commercialization of new biomedical products, including these important bioactive compounds, have been highlighted.